CALENDAR OF EVENTS. (Communications of the ACM, 2005)
This article presents information on various meetings, conferences and workshops that would be organized by the Association for Computing Machinery (ACM) from July-August 2005. Some of the events enlisted are: WICON 2005: First International Conference on Wireless Internet that would be held from July 10-15 in Budapest, Hungary, PPDP "05: Principles and Practice of Declarative Programming 2005 that would be held from July 11-13 in Lisboa, Portugal, WOSP '05: Workshop on Software and Performance 2005 that would be held from July 11-15 in Palma de Mallorca, Spain and others.